Kewenangan dan Peran Aparatur Sipil Negara (ASN) dengan konsep Maximus in Minimis dalam Mencegah dan Menekan Praktik Politik Uang - Soantahon, Sherwin Mikhael (Ministry of Home Affairs, 2024)
This study aimed to analyze the constrained role of the State Civil Apparatus (ASN) in suppressing the practice of money politics which contributes to high-cost elections during general elections. ASN's political activities are heavily restricted, limiting its ability to actively and directly engage in the electoral process. However, statutory provisions also mandate that ASN serve as both the implementer of public policy—an inherently political product—and as a unifying force for the nation. In its role as a unifier, ASN must actively contribute to ensuring that elections are conducted fairly and appropriately for the future of the nation. The object of this study was to examine the limited authority and role of ASN in suppressing the practice of money politics. The study employed a qualitative descriptive analysis to explore the issue from the ASN's perspective, focusing on the potential contributions of its authority and role in enhancing the quality of elections. The findings indicated that ASN can leverage its authority and role both individually and institutionally to suppress money politics practices. Individually, ASN members can contribute through socialization, advocacy, political education, information dissemination, and anti-money politics campaigns. Institutionally, contributions can be made by strengthening regulatory and policy frameworks, enhancing the integrity and capabilities of ASN personnel, conducting studies, analyses, and discussions to improve electoral process quality, and enforcing strict sanctions against perpetrators of money politics.